2004
DOI: 10.1002/jcp.20075
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled receptor agonist‐stimulated expression of ATF3/LRF‐1 and c‐myc and comitogenic effects in hepatocytes do not require EGF receptor transactivation

Abstract: Several agonists acting on G protein-coupled receptors (GPCR) enhance the mitogenic effect of epidermal growth factor (EGF) in rat hepatocytes, through mechanisms that have only partially been clarified. Results in various cells have led to the idea that a major mechanism for GPCR-mediated stimulation of cell growth is transactivation of receptor tyrosine kinases, particularly the EGF receptor (EGFR), leading to rapid phosphorylation of the EGFR and activation of downstream signaling pathways. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
4
12
0
Order By: Relevance
“…This is in agreement with our previous observation that cAMP does not mediate the proliferative effects of prostaglandins in the hepatocytes (Refsnes et al, 1995). Furthermore, although EP4 receptors have been found to stimulate cyclin D1 expression and phosphorylation of EGF receptor and extracellular signal-regulated kinase in murine hepatocytes (Kataoka et al, 2005), prostaglandins do not transactivate the EGF receptor in rat hepatocytes (Nilssen et al, 2004) but act to enhance subsequent stimulation of extracellular signal-regulated kinase and Akt by EGF (Dajani et al, 2007). In addition, we found no additive effects between sulprostone and misoprostol on DNA synthesis, suggesting lack of involvement of EP4 receptors.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with our previous observation that cAMP does not mediate the proliferative effects of prostaglandins in the hepatocytes (Refsnes et al, 1995). Furthermore, although EP4 receptors have been found to stimulate cyclin D1 expression and phosphorylation of EGF receptor and extracellular signal-regulated kinase in murine hepatocytes (Kataoka et al, 2005), prostaglandins do not transactivate the EGF receptor in rat hepatocytes (Nilssen et al, 2004) but act to enhance subsequent stimulation of extracellular signal-regulated kinase and Akt by EGF (Dajani et al, 2007). In addition, we found no additive effects between sulprostone and misoprostol on DNA synthesis, suggesting lack of involvement of EP4 receptors.…”
Section: Discussionsupporting
confidence: 93%
“…While ATF3 was reported to suppress cell growth in HeLa cells by blocking G 1 -S progression (9), there have been at least four studies that showed growth-promoting activity of ATF3 (2,29,33,41). ATF3 was found to be downstream of c-Myc and adenovirus-mediated overexpression of ATF3 in c-Mycdeficient fibroblasts resulted in increased CDK4 and CDK2 activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MMP levels are low in normal liver, but many-fold higher in hepatocellular carcinomas (20). Hence, MAPK activation by a GPCR agonist, angiotensin II, is dependent on MMP-mediated transactivation of the EGF-R in clonal C9 hepatic cells (38), but is independent of these proteins in native rat hepatocytes (24,48). Similarly, PI3K/Akt activity is high in H295R cells derived from human adrenal cortical carcinoma tissue, but low in primary cultures of BAG cells (54).…”
Section: Discussionmentioning
confidence: 99%